2013
DOI: 10.1109/mc.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

Broadening participation: The why and the how

Abstract: There are many reasons for striving to increase the representation of women in the computing field, but the most compelling one is the enhanced quality of the solutions diverse contributors can achieve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…had found that students' experiences in their CS courses affect their decisions to major in CS and their retention rates. Eney, Lazowska, Martin, and Reges (2013) and Cohoon et al (2013) found that many CS majors, especially females, had not intended to major in CS until they took their first CS course. Indeed, the present study found that positive experiences with the instructor in their first CS class predicted greater intention to take more CS classes.…”
Section: Experiences In Cs Classes and Role Modelsmentioning
confidence: 99%
“…had found that students' experiences in their CS courses affect their decisions to major in CS and their retention rates. Eney, Lazowska, Martin, and Reges (2013) and Cohoon et al (2013) found that many CS majors, especially females, had not intended to major in CS until they took their first CS course. Indeed, the present study found that positive experiences with the instructor in their first CS class predicted greater intention to take more CS classes.…”
Section: Experiences In Cs Classes and Role Modelsmentioning
confidence: 99%
“…Estudos mostram que existe uma série de fatores que levam ao desinteresse pela computação por parte das mulheres [Burge and Suarez 2005] [Beaubouef and Zhang 2011] [Eney et al 2013] [DuBow 2013] [Klawe 2013]. Dentre as principais causas estão a falta de "modelos femininos" na área, o fato das mulheres se sentirem excluídas em ambientes (estudantis ou profissionais) dominados por homens, a falta de incentivo para que sigam uma carreira na área e o fato de não se sentirem à vontade com a cultura da computação/tecnologia.…”
Section: Introductionunclassified
“…Though increased funding from both the private (e.g., Apple Inc. and the Gates Foundation) and public sectors (e.g., NSF), along with the launch of university programs (e.g., Alvarado and Dodds, 2010;Eney et al, 2013) and national initiatives specifically targeted at diversifying the pool of students exposed to The hypothesis addressed in the present paper is that that reframing introductory programming experiences from the discipline-specific to an approach that tackles real world questions across multiple disciplines will contribute to improving access to programming skills for students from a wider range of educational, social and economic backgrounds. Previous publications have described the development of a multidisciplinary data analysis course (Dierker, et al, 2012) aimed at engaging students in data-oriented projects that rely heavily on programming.…”
Section: Introductionmentioning
confidence: 99%